2009
DOI: 10.2460/ajvr.70.11.1323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical application of 1% diclofenac sodium liposomal cream on inflammation in healthy horses undergoing intravenous regional limb perfusion with amikacin sulfate

Abstract: Topical application of 1% diclofenac sodium liposomal cream to sites of IVRLP in healthy horses decreased inflammation as judged by visual assessment and ultrasonography. Decreased inflammation may allow extended use of IVRLP and may result in a reduction in pain in treated horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 10 publications
1
23
0
2
Order By: Relevance
“…This approach combines 2 methods, each previously found to limit systemic release of antibiotic to negligible levels, while concentrating drug within the metacapophalangeal joint . The volume perfused for IVRLP in our study (60 mL) has been found to produce high antimicrobial levels in synovial fluid, and is consistent with current clinical applications . Nonetheless, the lack of influence of IVRLP on local bioburden in our study justifies further investigation into pressures and volumes required to optimize wound bed perfusion.…”
Section: Discussionsupporting
confidence: 78%
“…This approach combines 2 methods, each previously found to limit systemic release of antibiotic to negligible levels, while concentrating drug within the metacapophalangeal joint . The volume perfused for IVRLP in our study (60 mL) has been found to produce high antimicrobial levels in synovial fluid, and is consistent with current clinical applications . Nonetheless, the lack of influence of IVRLP on local bioburden in our study justifies further investigation into pressures and volumes required to optimize wound bed perfusion.…”
Section: Discussionsupporting
confidence: 78%
“…Phlebitis is the most commonly reported complication with IVRLP, particularly with repeat IVRLP. 10,35 In addition, some pharmaceuticals result in vasculitis. 2 None of the 12 perfusions resulted in clinical signs of phlebitis or vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated daily venipuncture with a small-gauge needle was not associated with serious adverse effects, and topical anti-inflammatory drugs 18 or intraperfusate dimethylsulfoxide 1 were not used. Placement of indwelling IV catheters for A-RLP has been reported clinically 1 and recently evaluated.…”
Section: Discussionmentioning
confidence: 99%